IMPLIKASI ANALISIS LINGKUNGAN BISNIS TERHADAP STRATEGI PEMASARANDI HOTEL MELIA NUSA DUA BALI - Artajaya, Made; Candra Rismayati, Ni Luh (JURNAL KEPARIWISATAAN, 2018)
The increasing of hotel in tourism area of Nusa Dua has generated tight emulationlevel in hotel business. Intention of this research to identify and analyse environmental factor of internal and eksternal business for choosing the alternative pursuant strategy precisely by using technique analyse data qualitative. There are 10 factors becoming weakness and strength which is 5 factors becoming strength consist of strategic location, owning strong brand, many amount of room, competitif product price, traditional building concept and original Bali and 5 weakness factors are including old building age, room need rejuvenation, less adapting with new technology, less effective communications and less in exploiting of product potency. There are also 9 factors becoming threat and opportunity that is 5 factors becoming opportunity of Hotel Melia Bali which is including stable Indonesia economics, and new market segment as MICE. . Election of marketing strategy alternative pursuant to result of environmental analysis of business use SWOT Matrix and Ansoff Matrix.There are 3 especials marketing strategy which yielded that creates new packages and innovationin the form of product for special events (wedding, meeting and incentive).